τ Proteins in Serum Predict Outcome After Severe Traumatic Brain Injury - Liliang, Po-Chou; Liang, Cheng-Loong; Weng, Hui-Ching; Lu, Kang; Wang, Kuo-Wei; Chen, Han-Jung; Chuang, Jiin-Haur (The Journal of surgical research, 2010)
The identification of reliable outcome predictors after traumatic brain injury (TBI) is crucial. The objective of our study was to investigate the role of τ protein as a serum marker of TBI. Thirty-four patients with severe TBI (Glasgow Coma Scale [GCS] score at admission ≤ 8) were considered. The τ protein level in the blood samples obtained at the time of admission was measured. The outcome was assessed by using the Glasgow Outcome Scale (GOS) at 6 mo post-injury. Demographic, clinical, and laboratory variables were analyzed to study their effect on the outcome. τ Protein levels were higher in the poor outcome group (436.2 ± 473.6 pg/mL) than in the good outcome group (51.6 ± 81.5 pg/mL) (P < 0.0001). Univariate analyses demonstrated that poor outcome was significantly associated with a poor GCS score (P = 0.001), higher serum τ protein levels (P < 0.001), abnormal pupil light reflex (P = 0.013), and basal cistern compression on computed tomogram (CT) (P = 0.026). Multivariate analyses revealed that a poor GCS score (P = 0.049) and higher serum τ protein levels (P = 0.043) were independent prognostic factors for poor outcome. The receiver-operating characteristic (ROC) curve demonstrated that a τ protein level ≥ 114.5 pg/mL yielded 88% sensitivity and 94% specificity for predicting a poor outcome. These results suggest that in addition to GCS; serum τ protein levels may serve as indicators for the prediction of outcome following severe TBI. However; it should be viewed with caution because of the small sample size and wide standard deviations.